1998
DOI: 10.1136/sti.74.5.323
|View full text |Cite
|
Sign up to set email alerts
|

Patient referral outcome in gonorrhoea and chlamydial infections.

Abstract: Objective: To describe the outcome of patient referral at the STD clinic of the University Hospital Rotterdam. To study characteristics of heterosexual index patients and partnerships related to referral outcome. Methods: In 1994, patients with gonorrhoea and chlamydia were referred to public health nurses for interview and patient referral. Referral outcome was classified as "verified" if partners attended the STD clinic and as "believed" if partners were said to have attended elsewhere. Results: Of 454 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…Constraint as a result of stigma limited efforts to trace patients and partners. 20 Our study showed that 1.79 partners per index case were identified (range, 1-13), which was less than the number in one study 11 and more than the number in others. 9,11,21 Of 1293 partners identified, 301 (23.3%) partners were notified.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Constraint as a result of stigma limited efforts to trace patients and partners. 20 Our study showed that 1.79 partners per index case were identified (range, 1-13), which was less than the number in one study 11 and more than the number in others. 9,11,21 Of 1293 partners identified, 301 (23.3%) partners were notified.…”
Section: Discussionmentioning
confidence: 68%
“…20 Our study showed that 1.79 partners per index case were identified (range, 1-13), which was less than the number in one study 11 and more than the number in others. 9,11,21 Of 1293 partners identified, 301 (23.3%) partners were notified. This could be underestimated, because some partners could have used a different name, could have visited different doctors when they attended our clinic, or they could have visited other healthcare services such as a family planning and gynecologic department or even other STD-providing services, including private STD providers.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…I couldn't see myself doing that (Interview 9, case, from Dublin, hairdresser, 40 years old) Moving on to the issue of casual sex, much has been written in the public health literature about the 'problem' of MSM and casual sex. It is widely reported that MSM are less able to provide sexual health advisers with contact details of their partners and, therefore, relative to women and the heterosexual population, are considered to be poor at complying with PN (Munday et al 1983, van Duynhoven et al 1998, Rogstad et al 1999, Whittington et al 2002, Hogben et al 2005. In our study, we also found some evidence to suggest that some MSM had difficulties in complying with PN because of the casual nature of some of their sexual encounters.…”
Section: Experiences Of Pn -Attending Clinics and Informing Otherssupporting
confidence: 34%